Diagnoza: pojęcie, cechy diagnostyczne i zastosowania w badaniach edukacyjnych - Banaszak , Sławomir (Studia Edukacyjne, 2018)
The classic understanding of diagnosis is connected with the practical activity, mainly in medicine. Currently, however, diagnostics have a much wider meaning. It covers not only natural science but also technical sciences. Social sciences, in turn, included diagnosis in the typology of empirical research, mainly about a practical goal, but more and more often also cognitive. The problems of assessment within diagnosis processes, type of social research and the diagnosis as the stage of any research in social sciences are revealed by the author. The paper ends with the emphasizing of diagnosis features and its educational applications in modern research plans.